2021
DOI: 10.1039/d1sm00195g
|View full text |Cite
|
Sign up to set email alerts
|

Gel-to-gel non-variant transition of an organogel caused by polymorphism from nanotubes to crystallites

Abstract: An amide based gelator forms gels in trans-decalin. Below concentrations of 1 wt. % the gels melt at temperatures varying with concentration. Above concentration of 1 wt. %, upon heating,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The main difficulty comes from the fact that the internal structure of the organogels can be easily destroyed. Organogels are lyotrop systems that can undergo polymorphic phase transitions upon concentration change. Hence, scanning electron microscopy (SEM) was not a suitable technique as the solvent needs to be removed prior to the observation (leading to a xerogel). To keep intact as much as possible the structure of the gel, cryo-SEM measurements were performed using a JEOL High Resolution 6700F SEM.…”
Section: Methodsmentioning
confidence: 99%
“…The main difficulty comes from the fact that the internal structure of the organogels can be easily destroyed. Organogels are lyotrop systems that can undergo polymorphic phase transitions upon concentration change. Hence, scanning electron microscopy (SEM) was not a suitable technique as the solvent needs to be removed prior to the observation (leading to a xerogel). To keep intact as much as possible the structure of the gel, cryo-SEM measurements were performed using a JEOL High Resolution 6700F SEM.…”
Section: Methodsmentioning
confidence: 99%
“…Gel-to-gel transition was observed in different systems upon ageing. HUB-4 ( Figure 18 ) forms gel in alkanes with concentration > 0.5 wt% in various alkanes [ 58 ].…”
Section: Gel–gel Transitionsmentioning
confidence: 99%
“…The c - T phase diagram of HUB-4 / trans- decalin upon heating ( Figure 20 ) was established over a decade of concentrations by the same techniques [ 58 ]. The structure and the relative stability of gel 1 and gel 2 were studied by SEM and X-ray scattering.…”
Section: Gel–gel Transitionsmentioning
confidence: 99%
“…32 We have recently shown that palmitoylethanolamide, an endogenous fatty amide sold as a nutraceutical, is able to gel edible oils. 33…”
Section: Introductionmentioning
confidence: 99%
“…32 We have recently shown that palmitoylethanolamide, an endogenous fatty amide sold as a nutraceutical, is able to gel edible oils. 33 For applications in food chemistry, it is necessary to know and control the thermal stability of the gels, their mechanical properties at different temperatures (e.g. at fridge and body temperature) and their phase behaviors.…”
Section: Introductionmentioning
confidence: 99%